(untitled) (Eastern Medical College Journal, 2026)
Background: Adverse drug events (ADE) are major health problems that occur in children and adults. Some drugs are commonly prescribed in both paediatric and adult patients and safety of these drugs is a major concern. The active monitoring system is more practical for obtaining detailed data on individual adverse event reports than a passive reporting system. This study aimed at the detection of suspected adverse events (SAE) in paediatric and adult hospitalized patients by active monitoring, to find out is there any difference in the incidence of SAE between these two age group populations. Materials and Methods: At first through the cross-sectional study, three commonly prescribed drugs, ceftriaxone, prednisolone, and paracetamol, were identified. Based on inclusion and exclusion criteria, 219 paediatric and 234 adult patients were enrolled. Then, a prospective observational study was conducted based on a solicited adverse event list to determine the SAE of these drugs among paediatric and adult hospitalized patients. Results: After active monitoring of all enrolled patients by maintaining an adverse event checklist, 7.8% of paediatric patients and 5.02% of adult patients experience SAE. In the case of ceftriaxone, paediatric patients (11.26%) experience more SAE than adult patients (7.05%). In paracetamol, no adult patient experience SAE. In prednisolone, the SAE detection rate is almost similar in both adults (6.02%) and paediatric patients (4.93%). By WHO-UMC causality categories, 20% were certainly ADEs, 40% were probable/likely and 40% were possible ADEs in paediatric patients treated with ceftriaxone. On the other hand, one third of the cases were certain and the remaining had possible relationships with the drug in adult patients. In the case of prednisolone, 75% of adverse events were mild and possible event. In paracetamol, 1.4% of paediatric patients experienced ADE which was a possible reaction and mild in severity. In this study, there is no statistically significant difference in ADE detection rate in both paediatric and adult patients. However, there is an overall increase in ADE detection rate in paediatric patients. Conclusion: The adverse event detection rate of commonly prescribed drugs was higher in paediatric hospitalized patients compared to adult patients through the active monitoring method. Eastern Med Coll J. July 2025; 10 (2): 137-142